KONSERVASI DAMAR MATA KUCING (Shorea javanica) BERBASIS MASYARAKAT DI ZONA TRADISIONAL TAMAN NASIONAL BUKIT BARISAN SELATAN - Yulizar .; Agus Hikmat; Nandi Koesmayandi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Potential damar tree (Shorea javanica) in the traditional zone of Bukit Barisan Selatan National Park (BBSNP). Based on the results of the analysis of vegetation data is conducted by making 50 plots, the abundance distribution in phase 56 individual trees / hectare. Shorea javanica tree is located in the zone of the trees that was planted with resin by Krui community. The value of dominance species was of 13.1 m² / ha. Potential of tree sap resin, which was produced in the tradisional, was estimated 59 kg per hectare. Distribution of the resin in the traditional zone TNBBS was about 446 hectare which was located along the Liwa-Krui. Management form for the resin treee in the research villages, Pekon Labuhan Mandi and Pekon Penengahan, was relatively the same. The altitude difference in growth trees and age affected production of latex. Based on the factor analysis results, factor 1 was the greatest influence factor for the decision-gum resin cat eye. Variables in a single factor, income and broad repong, were the most influential variable than the other factors. Development of agroforestry activities in BBSNP be in implementation as a priority policy direction and management strategies TN Under Regulation No. 28 of 2011 on the Management of Nature Reserves and Nature Conservation in Article 35 paragraph 1 and paragraph 2 letter f Efforts to improve the welfare of forest communities through conservation amber Shorea javanica and community-based sustainability and maintain the diversity of plants and wildlife. Keyword : Community, Distribution, Management, Potential, Shorea javanica,Traditional zone.